.2020- دراسة قياسية لمحددات الطلب النقدي في الجزائر 19: An empirical study of the determinants of monetary demand in Algeria 1990-2020. - جمعة رضوان (Journal of North African Economies, 2025)
This study aims to know the determinants of monetary demand for Algeria in the long and short terms, so We used the cointegration methodology and impulse response functions. The results indicated the existence of a long-term relationship, the monetary demand is positively affected by the real GDP and the inflation rate, and negatively by the interest rate. In the short term, we used the impulse response functions, which indicated that monetary demand is positively affected by real GDP, and negatively affected by the rate of inflation and interest.